2020
DOI: 10.1186/s12906-020-03100-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and in vitro anti-salmonellal activity of compounds from stem bark extract of Canarium schweinfurthii

Abstract: Background Bacteria belonging to the Salmonella genus are major concern for health, as they are widely reported in many cases of food poisoning. The use of antibiotics remains a main stream control strategy for avian salmonellosis as well as typhoid and paratyphoid fevers in humans. Due to the growing awareness about drug resistance and toxicities, the use of antibiotics is being discouraged in many countries whilst advocating potent benign alternatives such as phyto-based medicine. The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…The inhibition of Salmonella growth by different extracts of B. rufescens may be due to the presence of phenolic compounds. This result corroborates the work of Sokoudjou et al [24] who showed that phenolic compounds such as gallic acid and scopoletin were active (MIC ranging from 16 to 128 µg/ml) against ST, STM and S. Typhi 6539. Antibacterial substances can be classified as bactericidal, when the BMC/MIC ratio ≤ 4 or bacteriostatic, when the MBC/MIC ratio > 4 [25].…”
Section: Discussionsupporting
confidence: 91%
“…The inhibition of Salmonella growth by different extracts of B. rufescens may be due to the presence of phenolic compounds. This result corroborates the work of Sokoudjou et al [24] who showed that phenolic compounds such as gallic acid and scopoletin were active (MIC ranging from 16 to 128 µg/ml) against ST, STM and S. Typhi 6539. Antibacterial substances can be classified as bactericidal, when the BMC/MIC ratio ≤ 4 or bacteriostatic, when the MBC/MIC ratio > 4 [25].…”
Section: Discussionsupporting
confidence: 91%
“…However, upregulation of these receptors can disrupt immune balance and lead to a continuous inflammatory state and poor signaling to the adaptive system [ 29 ]. Polyphenols in general can mitigate inflammatory diseases related to infections via the modulation of the signaling pathways that are mediated by pathogen recognition receptors [ 30 , 31 ]. Thus, polyphenols were found to effectively regulate NF-κβ activation and reverse TLR gene over-expression in exposed organisms [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…One (1) kg of the total powder was removed and worm in water (2 L) which was remove from the heat source for 15 minutes for the infusion while for the decoction we mixed one kg of powder with 2L of water and allow both to boil for 15 minutes. Part (3,14 kg) of powder was also use to prepare hydroethanolic extracts (95%, 75%, 55% and 35%) according to the protocol described by Sokoudjou et al, [20]. After filtration, the obtained filtrates were evaporated under reduced pressure using a rotary evaporator to yield the extracts.…”
Section: Preparation Of Crude Extractsmentioning
confidence: 99%